2017
DOI: 10.4143/crt.2016.495
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy with Gemcitabine and Cisplatin Followed by Simultaneous Integrated Boost–Intensity Modulated Radiotherapy with Concurrent Gemcitabine for Locally Advanced Unresectable Pancreatic Cancer: Results from a Feasibility Study

Abstract: Purpose This study assessed the feasibility and compliance of induction chemotherapy with gemcitabine and cisplatin followed by simultaneous integrated boost–intensity modulated radiotherapy (SIB-IMRT) with concurrent gemcitabine in patients with locally advanced unresectable pancreatic cancer.Materials and Methods In this trial, patients received induction chemotherapy consisting of gemcitabine (1,000 mg/m2) and cisplatin (25 mg/m2) on days 1, 8, and 15 of each treatment cycle. Patients were subsequently trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…However, the median OS and incidence of grade ≥3 toxicity in the present study were at the higher and lower end of the wide range reported previously, respectively. 9 15 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the median OS and incidence of grade ≥3 toxicity in the present study were at the higher and lower end of the wide range reported previously, respectively. 9 15 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…The prescribed doses for PTV1 and PTV2 were 45 GyE (EQD2, 54.4 GyE 10 ) and 30 GyE (EQD2, 32.5 GyE 10 ) in 10 fractions, 5 times a week, respectively ( Figure 1 ). The dose–volume constraints for the normal tissues have been described in our previous reports 9 , 20 23 : The maximum dose to the spinal cord were <27 GyE; the absolute volumes of the stomach and esophagus receiving ≥37 GyE were <2 cm 3 ; the absolute volumes of the duodenum and bowel receiving ≥35 GyE were <2 cm 3 ; the relative volumes of the liver receiving ≥27 GyE were below 60%; and the relative volumes of the kidney receiving ≥18 GyE were below 35%. The dose–volumetric parameters for target volumes and OARs are summarized in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of patients with head and neck squamous carcinoma, Mazurek, et al 12 reported that higher levels of cfDNA were observed in patients with advanced N stage and overall. Woo, et al 13 reported that cfDNA declined significantly after concurrent chemoradiotherapy in a study of patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the kinetics of circulating tumor-derived DNA in serum or plasma revealed that the amounts of cfDNA were found to increase at the beginning of RT and to decrease to or below initial levels by the end of treatment. 12 13 19 31 Therefore, the persistent elevation of cfDNA after treatment completion may indicate the presence of remnant lesions or progression in other sites. 32 33 After adjusting for other factors, a high post-RT cfDNA level was revealed to be an independent factor for poor intrahepatic tumor control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation